2020
DOI: 10.1001/jamaoncol.2019.5233
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Evidence for Association of Acupuncture and Acupressure With Improved Cancer Pain

Abstract: IMPORTANCE Research into acupuncture and acupressure and their application for cancer pain has been growing, but the findings have been inconsistent. OBJECTIVE To evaluate the existing randomized clinical trials (RCTs) for evidence of the association of acupuncture and acupressure with reduction in cancer pain.DATA SOURCES Three English-language databases (PubMed, Embase, and CINAHL) and 4 Chinese-language biomedical databases (Chinese Biomedical Literature Database, VIP Database for Chinese Technical Periodic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
256
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 277 publications
(262 citation statements)
references
References 78 publications
4
256
1
1
Order By: Relevance
“…While trials studying acupuncture-related alleviation of cancer-related pain have not been conclusive, a recent systemic review of randomized clinical trials found that the use of acupuncture was significantly associated with a reduction in cancer-related pain, and decreased analgesic use. [16] Additionally, acupuncture has shown promise in improving symptoms including fatigue, indigestion, hot flashes, chemotherapy-induced nausea and vomiting, radiation-related xerostomia, and other cancer-or treatment-related ailments. [17][18][19][20]…”
Section: Discussionmentioning
confidence: 99%
“…While trials studying acupuncture-related alleviation of cancer-related pain have not been conclusive, a recent systemic review of randomized clinical trials found that the use of acupuncture was significantly associated with a reduction in cancer-related pain, and decreased analgesic use. [16] Additionally, acupuncture has shown promise in improving symptoms including fatigue, indigestion, hot flashes, chemotherapy-induced nausea and vomiting, radiation-related xerostomia, and other cancer-or treatment-related ailments. [17][18][19][20]…”
Section: Discussionmentioning
confidence: 99%
“…For example, acupuncture and Chinese herbal medicines are recommended for cancer pain and serve to reduce opioid abuse. [27][28][29][30][31][32][33] TCM can also improve digestive symptoms, such as nausea, caused by radiotherapy and chemotherapy. [34][35][36] Moreover, psychiatric symptoms, such as anxiety and depression, in methamphetamine addicts during abstinence can be improved with electroacupuncture, 37 whereas depression-related insomnia and insomnia in cancer survivors can be treated with acupuncture, herbal medicines, and/or t'ai chi.…”
Section: Suggestionsmentioning
confidence: 99%
“…to the cancer treatments. [19][20][21][22][23][24] Most National Cancer Institute-designated comprehensive cancer centres have begun offering acupuncture. In addition, systematic reviews showed that acupuncture and/or acupressure is significantly associated with reducing chronic cancerrelated pain and decreasing the use of analgesics.…”
Section: Open Accessmentioning
confidence: 99%